The effect of 0.25% levobupivacaine and 0.25% ropivacaine in fascia iliaca block in elderly patients with fracture femur given before positioning for subarachnoid block - Gupta, Neetu; Jain, Pooja; Kapadia, M.; Sanwatsarkar, Sadhana; Saxena, Dipti; Maheshwari, Meghna (International Journal of Research in Medical Sciences, 2017)
Background: Positioning of elderly patients with fracture femur for subarachnoid block (SAB) is a challenging task, both for the patient and anesthesiologist. Severe pain not only adds to the morbidity but also alters the success rate of SAB as appropriate positioning becomes difficult. Fascia iliaca compartment block (FICB) is a simple, rapid, effective and safe method for achieving excellent pain relief. The purpose of this study is to compare the efficacy of 0 .25% of levobupivacaine and 0.25% ropivacaine in FICB on reducing preoperative and postoperative pain and analgesic consumption in lower limb surgery. Methods: 60 elderly patients of ASA class I-III scheduled for elective fracture femur surgery were enrolled in the study and randomly divided into two groups. Group L received 30ml 0.25% levobupivacaine in FICB while Group R received 0.25% ropivacaine in FICB 15min before SAB. Parameters recorded were blood pressure, heart rate, visual analogous scale (VAS), quality of positioning and time to first rescue analgesia. VAS was noted before and after performing FICB and at the time of positioning for subarachnoid block (SAB). Results: The VAS score at different time interval and time to first rescue analgesia were comparable (P >0.05). Quality of positioning was also similar in both the groups (P >0.05). Conclusions: The study demonstrates that levobupivacaine and ropivacaine produce comparable preoperative and postoperative analgesia when used for FICB.